2015
DOI: 10.3109/0886022x.2015.1056063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of percutaneous nephrolithotomy on renal functions in children: assessment by quantitative SPECT of99mTc-DMSA uptake by the kidneys

Abstract: Tc-DMSA) examinations before and 3 months after surgery. Results: The mean age was 9.5 years (range, 3-16), and the mean stone size was 3.4 cm (range, 2-6.5). Of the cases, 39 (95%) were managed as being stone-free after a single session of PNL. After additional treatment procedures, 40 (97.5%) of the cases were managed as being stone-free. Of the 41 renal units, new focal cortical defects on 99m Tc-DMSA scans were seen in 4 (9.7%) patients. Total relative uptake in the treated kidneys increased from 42.3% to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…One of the most essential treatment alternatives for renal stones in childhood is PCNL [ 20 ]. Cicekbilek I et al investigated the effect of PCNL performed in childhood on renal functions in their study involving 40 patients and 41 renal units [ 7 ]. According to this study, out of the 41 renal units examined, new focal cortical defects were observed on (99m)Tc-DMSA scans in four (9.7 %) patients following PCNL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most essential treatment alternatives for renal stones in childhood is PCNL [ 20 ]. Cicekbilek I et al investigated the effect of PCNL performed in childhood on renal functions in their study involving 40 patients and 41 renal units [ 7 ]. According to this study, out of the 41 renal units examined, new focal cortical defects were observed on (99m)Tc-DMSA scans in four (9.7 %) patients following PCNL.…”
Section: Discussionmentioning
confidence: 99%
“…PCNL is considered a primary option in the pediatric period, similar to adults, due to its effective stone-free rate, particularly in the surgical treatment of renal stones larger than 2 cm [ 6 ]. Studies demonstrate the impact of PCNL on renal functions in children [ 7 ]. However, according to our research, there is a lack of literature studies examining the impact of the most preferred procedure in childhood renal stone surgery, RIRS, on renal functions in children.…”
Section: Introductionmentioning
confidence: 99%
“…In general, pyelolithotomy is considered as a kind of neuron sparing urinary stone removal therapy, causing less parenchyma damage than other techniques [ 20 ]. PCNL was also evidenced to have minimal impact on regional or global renal function without significant postoperative alteration [ 14 16 , 21 23 ]. However, there is lacking cohort study to compare postoperative ESRD between PCNL and open pyelolithotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Renal stone is a common and serious medical condition, Percutaneous nephrolithotomy (PCNL) is considered to be the gold standard management for it, as has low retreatment rate, shorter operation time, shorter length of hospital stay, and quick recovery [1][2][3][4] Despite rapid popularization of PCNL, questions about the long-term effects of PCNL is still unknown. The dilatation of the tract directly injures the renal parenchyma, leading to the formation of scar and consequent wound contracture.…”
Section: Introductionmentioning
confidence: 99%
“…Renal stone is a common and serious medical condition, Percutaneous nephrolithotomy (PCNL) is considered to be the gold standard management for it, as has low retreatment rate, shorter operation time, shorter length of hospital stay, and quick recovery 14…”
Section: Introductionmentioning
confidence: 99%